A Comparative Study of Imidazolium-Based Ionic Liquid-Single-Walled Carbon Nanotube Composites with Enhanced Conductivity Properties for Supercapacitor Applications. (8th September 2020) - Hemraj-Benny, Tirandai; Lall-Ramnarine, Sharon I.; Suarez, Sophia; Paterno, Domenec; Ramdihal, Jasodra D.; Sumner, Rawlric; Urena, Katelyn; Wishart, James F.
Abstract : Mixtures of ionic liquids (ILs) containing single-walled carbon nanotubes (SWCNTs) were prepared and characterized to obtain electrolytes with optimized transport properties for use in energy storage devices such as supercapacitors. Imidazolium ILs bearing cations with side chains of different functionality, coupled with bis(trifluoromethylsulfonyl)amide (NTf2 - ) or bis(fluorosulfonyl)amide (FSA - ) anions, were used in mixtures containing up to 5 wt% SWCNTs. At and above 2 wt% nanotube loading, the mixtures exhibited higher conductivities than the pure ILs, in spite of the extremely high viscosities. Loadings of 5 wt% produced very high conductivities, and studies of the temperature dependence indicated a change in the charge transport mechanism between 2 and 5 wt% loading. At 5 wt% loading, the highest conductivities (up to 540 mS/cm at 25°C) were obtained for the ILs containing the NTf2 - anion. These results can significantly contribute to the development of improved energy storage devices.